PELAKSANAAN TUGAS KEPOLISIAN DALAM PENANGGULANGAN KONFLIK SOSIAL DI WILAYAH POLDA SUMUT - Lestari Victoria Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
Aspect of social conflict that needs to be considered is violence arising from social conflict. Conflict management aims at preventing how violence does not occur and conflict parties can handle and resolve their conflicts without using violence. Government Regulation Number 2 Year 2015 concerning Act Implementing Regulation Number 7 2012 concerning Handling Social Conflict was made to protect and provide a more optimal sense of community security. Government regions in preventing conflicts optimize peaceful dispute resolution through deliberation for consensus and can involve participation of the society.